Nature's Calendar: Plant's Calendar - phenological observations made by Citizen Scientists - Langvall, Ola; Dahl, Åslög; Johansson, Jacob; Bolmgren, Kjell; Swedish Botanical Association; Swedish Beekeepers Association (Swedish University of Agricultural Sciences, 2022)
Nature's Calendar (www.naturenskalender.se, in Swedish only) is run by the Swedish National Phenology Network, a consortium of Swedish universities, governmental agencies and NGO:s. The Swedish University of Agricultural Sciences hosts the network. The main task for the Nature's calendar is to collect observations of different spring and autumn signs appearing during the vegetation season.

Data about the nature's calendar is collected in two ways, the long-term environmental monitoring through "Calendars", where phenological observations are reported all through the year, and through "Checks", where phenology observations are reported during short-time campaigns, giving a snapshot of the phenological status at a certain time of the year. The long-term environmental monitoring is performed by citizen scientists and professional observers at research stations and like. Three calendars have been launched in the Nature's Calendar; the Plant's Calendar (from 2008), the Bird's Calendar (from 2016) and the Beekeeper's Calendar (between 2015 and 2018).

Aims
Phenological changes in nature gives the most obvious signs of the biological effect of climate change. Spring signs, autumn signs, the start, end and length of the growing season, and many other signs in nature are basic properties of ecosystems. Also, the interaction between different organisms, e.g. flowering plants and pollinators, are affected if the nature's calendar changes. Observations reported to the Nature's Calendar can be compared to similar observations collected for more than 100 years ago (see Swedish Historical Phenology Dataset, published in another place at this platform), to detect evidence of phenological shifts over time that can be connected to climate change.

The aim of the Nature's Calendar is to collect phenological data from the first spring sign to the last autumn sign, to be able to offer nation-wide data to everyone interested, to facilitate research, environmental assessments, the evaluation of environmental goals, etc, to be better prepared to meet the effects of climate change. For example, the data collected in Nature's Calendar is continuously used to evaluate the Swedish environmental objective Reduced Climate through the indicator called ”Growing Season” (www.slu.se/vaxternasvaxtsasong).

Three datasets are made available through SND: the Plant's Calendar, the Beekeeper's Calendar and the Spring Check datasets. They all originate from the same database in the Nature's Calendar, while the Bird's Calendar observations are published through the Swedish Species Observation System Portal (www.artportalen.se).

In the Plant's Calendar, Citizen Scientist's have reported observations of how
- budburst and leaf development (broadleaves)
- budburst and shoot elongation (conifers)
- flowering
- ripening of fruits and berries
- seed dispersal
- autumn colors
- leaf shedding
develop during the growing season.

The aim with the data collection is to obtain nationwide data that can provide information to understand, track changes and predict effects of climate change on natural plants in Sweden.

The dataset includes one file with observation data (plants_calendar_2008-2021.csv), one file with the full species list used by the observers (plants_calendar_specieslist_2008-2021.csv), one file with the full list of phenological phases and sub-phases that observers can report (plants_calendar_phaselist_2008-2021.csv), one PDF file (metadata_plants_calendar_2008-2021.pdf) with metadata that describes how the above mentioned CSV files are related and how the included parameters should be interpreted, and one PDF file (vaxtkalendern_fenologimanual_2021.pdf) which describes the protocol used by those included in the phenology observer programme, i.e. the observations indicated as high quality (in Swedish, only). The observation data file includes totally 148 481 observations.

The data collection in the "Nature's Calendar - Plant's Calendar" started in 2008, but some observations made at a few locations at earlier dates have also been registered in the database, so this dataset includes a few records already from 1980 and forward.

Coordinates of the observation locations have been made diffuse, partly to make it impossible to trace back the observations to the observer (coordinates are rounded to 3 decimals), partly to make tracing back to the original location of protected species impossible (coordinates are rounded to 1.5 decimals = > 6 km diffusion), as to the rules for publicly handling of nationally protected species (see https://www.artdatabanken.se/var-verksamhet/fynddata/skyddsklassade-arter/).

Naturens kalender (www.naturenskalender.se) drivs av Svenska fenologinätverket, som är ett nätverk med flera universitet, myndigheter och föreningar. SLU, Sveriges lantbruksuniversitet, är nätverkets huvudman.
Huvuduppgiften för Naturens kalender är att samla in observationer av vårtecken, hösttecken och annat i naturens kalender.

Data om naturens kalender samlas in på två olika sätt. Dels bedrivs en långsiktig miljöövervakning i form av ”kalendrar” där rapporter om fenologiska observationer samlas in över hela året, dels genomför vi korta ”kollar” där vi tar en ögonblicksbild av naturens kalender i landet vid en viss tidpunkt på året. Den långsiktiga miljöövervakningen genomförs av frivilliga och professionella medborgarforskare, s.k. fenologiväktare, i Växtkalendern (från 2008), Fågelkalendern (från 2016) och Bikalendern (2015-2018).

Motiv och syfte
Fenologiska förändringar i naturen är den tydligaste biologiska effekten av en klimatförändring. Vårtecken, hösttecken, växtsäsongens start, slut, längd och andra händelser i naturens kalender är kopplade till grundläggande egenskaper hos ekosystemen. Samspelet mellan olika arter, t.ex. växterna och deras pollinatörer, påverkas också, om naturens kalender ändras. En förändring av naturens kalender får också effekt för landets alla pollenallergiker eftersom både tidpunkten och längden på pollenperioden ändras. Observationer som samlas in i Naturens kalender kan jämföras med motsvarande observationer som gjordes för över 100 år sedan (se Svenskt historiskt fenologidataset, som publicerats på annan plats på SND), för att upptäcka fenologiska förändringar över tid som kan bero på klimatförändringar.

Målet med Naturens kalender är att samla in data om allt från första vårtecken till sista hösttecken, så att vi kan erbjuda landsomfattande data till alla intresserade, för att underlätta forskning, miljömålsarbete och information och göra oss bättre rustade att möta klimatförändringens effekter. Data från Naturens kalender används exempelvis till uppföljningen av de svenska miljömålen genom miljömålsindikatorn ”Växternas växtsäsong” (www.slu.se/vaxternasvaxtsasong).

Via SND tillgängliggörs tre dataset: Växtkalendern, Bikalendern och Vårkollen, som alla kommer från samma databas i Naturens kalender. Fågelkalenderns data publiceras i Artportalen (www.artportalen.se).

I Växtkalendern har medborgarforskare rapporterat in observationer av hur
- blomning
- lövsprickning
- barrträds skottskjutning
- bär- och fruktmognad
- fröspridning
- höstlövens färger
- lövfällning
utvecklas under växtsäsongen.

Målet är att bidra med landsomfattande data för att bättre kunna följa, förstå och förutse klimatförändringens effekter på vilda växter i Sverige.

Datasetet innehåller en fil med observationsdata (plants_calendar_2008-2021.csv), en fil med den kompletta artlistan som används av observatörerna (plants_calendar_specieslist_2008-2021.csv), en fil med kompletta listan över de fenologiska faser som observatörerna kan rapportera (plants_calendar_phaselist_2008-2021.csv), en PDF-fil (metadata_plants_calendar_2008-2021.pdf) med metadata som beskriver hur ovanstående filer relaterar varandra samt beskriver ingående variabler, samt en PDF-fil (vaxtkalendern_fenologimanual_2021.pdf), som är den manual som s.k. fenologiväktare lovat följa (d.v.s. de som rapporterar med en högre kvalitet). Observationsdatafilen innehåller totalt 148 481 observationer.

Observationsdatafilen kan användas fristående, övriga kan ses som kompletterande information för att förstå innehållet i denna (liksom att få fenologiska faserna i engelsk översättning).

Datainsamlingen i "Naturens kalender - Växtkalendern" påbörjades 2008, men ett antal observationer från enskilda observationsplatser som gjorts vid tidigare datum har också registrerats i databasen, varför observationsdatafilen innehåller enstaka observationer ända från 1980 och framåt.

Koordinaterna för observationsplatserna har gjorts diffusa, dels för att ta bort möjligheten att spåra observatören (avrundning till 3 decimaler), dels för att ta bort möjligheten att spåra platsen för observationer av skyddsvärda arter (avrundning till 1,5 decimaler = >6 km diffusion) i enlighet med reglerna för publik hantering av nationellt skyddade arter (se https://www.artdatabanken.se/var-verksamhet/fynddata/skyddsklassade-arter/).
Naturens kalender: Växtkalendern - fenologiska observationer av medborgarforskare
Keywords: Plant Phenology; Plant Phenology; bee; bin; Species distribution; Arters utbredning; spring (season); spring; phenology; citizen science; medborgarforskning; Spring sign; Vårtecken; phenology; fenologi; Climate Research; Klimatforskning; Environmental Sciences; Miljövetenskap; Ecology; Ekologi; Biota; Biologi och ekologi